2019
DOI: 10.1177/0018720819889533
|View full text |Cite
|
Sign up to set email alerts
|

Does Using Multiple Computer Monitors for Office Tasks Affect User Experience?

Abstract: Objective To compare the impact of multiple computer monitor configurations on health and performance outcomes compared to the use of a single monitor. Background Multiple monitor configurations are used in office settings to promote increased productivity by providing more screen space; however, it is unknown if there are health-related trade-offs to increased productivity. Method A systematic review was conducted according to the PRISMA statement guidelines and adapted the best evidence synthesis. Results Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…Recently, Gallagher et al [42] conducted an interesting study to compare the performance and impact of multiple computer monitor with the use of a single monitor. There was a strong evidence that users prefer dual-monitor displays.…”
Section: Fundamentals and Aims Of Ggimentioning
confidence: 99%
“…Recently, Gallagher et al [42] conducted an interesting study to compare the performance and impact of multiple computer monitor with the use of a single monitor. There was a strong evidence that users prefer dual-monitor displays.…”
Section: Fundamentals and Aims Of Ggimentioning
confidence: 99%
“…These curved UW displays may replace dual and multi-display configurations. A systematic review found that dual-display configurations increase user satisfaction and productivity but may also result in neck rotation compared to a single display (Gallagher et al, 2021). This is of concern because previous work has shown that the frequency of neck rotation movements longer than 4 s is associated with neck pain and neck pain at follow-up (Coenen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found that the experimental design of studies on dual displays has led to conflicting results for user posture (Gallagher et al, 2021). Of the seven biomechanical studies included in this review, three had their participants centered on the displays (Farias Zuniga & Côté, 2017; Nimbarte et al, 2013; Stringfellow, 2007), one had a primary display and an off-center secondary display (Szeto et al, 2014), and three did not mention the configuration (Estember et al, 2015; Shamsul Bahri et al, 2016; Yoo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Multi and ultrawide (UW) display advancements have outpaced evidence-based usage guidelines that take into account both ergonomics and performance. A systematic review of dual display usage found strong evidence that users prefer dual displays over single displays (Gallagher, Cameron, De Carvalho, & Boule, 2019). While performance has been assessed in larger displays, biomechanical studies have only assessed displays 21" or smaller (Gallagher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of dual display usage found strong evidence that users prefer dual displays over single displays (Gallagher, Cameron, De Carvalho, & Boule, 2019). While performance has been assessed in larger displays, biomechanical studies have only assessed displays 21" or smaller (Gallagher et al, 2019). As a result, this study assessed the effects of display configuration on biomechanics and performance when using larger and ultrawide displays.…”
Section: Introductionmentioning
confidence: 99%